2015
DOI: 10.1007/s12028-015-0108-y
|View full text |Cite
|
Sign up to set email alerts
|

High-Sensitive Troponin T and N-Terminal Pro B-Type Natriuretic Peptide for Early Detection of Stress-Induced Cardiomyopathy in Patients with Subarachnoid Hemorrhage

Abstract: The cardiac biomarkers, hsTnT and NTproBNP, are increased early after SAH and levels are considerably higher in patients with SIC. These biomarkers are useful for screening of SIC, which could make earlier diagnosis and treatment of SIC in SAH patients possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 40 publications
4
24
0
Order By: Relevance
“…In a study of 135 SAB patients undergoing echocardiography TTS was found in 25 (18.5%) [9]. TTS was associated with peak-proBNP levels in this study [9]. In a study of 828 SAB patients undergoing echocardiography 19 (0.8%) developed TTS [10].…”
supporting
confidence: 49%
See 1 more Smart Citation
“…In a study of 135 SAB patients undergoing echocardiography TTS was found in 25 (18.5%) [9]. TTS was associated with peak-proBNP levels in this study [9]. In a study of 828 SAB patients undergoing echocardiography 19 (0.8%) developed TTS [10].…”
supporting
confidence: 49%
“…Risk factors for TTS were high Hunt-Hess-score (HHS), smoking, and old age [8]. In a study of 135 SAB patients undergoing echocardiography TTS was found in 25 (18.5%) [9]. TTS was associated with peak-proBNP levels in this study [9].…”
supporting
confidence: 45%
“…Takotsubo syndrome is extensively reported in cerebral hemorrhage and traumatic brain injury. [30][31][32] Cardiac dysfunction in sepsis is well described but is most frequently described as general LV dysfunction but RWMA is occasionally reported. 33,34 However, it is plausible that a significant proportion of patients with in septic cardiomyopathy might in fact suffer from the TS and sepsis is reported as a frequent trigger of TS.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al found that only 21% of SCM patients had a higher cTnI level on the day of admission [20]. This may be the reason why most SCM patients have a modest rise in cTnI concentrations followed by a rapid decline in cTnI levels because of the short half-life of cTnI in SCM patients [23,24]. Therefore, measuring cTnI early after admission is recommended as it is the preferred biomarker for assessing early myocardial injury and for early detection of SCM.…”
Section: Discussionmentioning
confidence: 99%